Base components for building significant learning (2020)
This paper presents the construction of student learning of the Bachelor of Religious Education, identifying in significant learning the bases for such construction in integration of different disciplines such as psychology, pedagogy, philosophy and oral and written expression as meeting point. The question about knowledge is addressed by showing how the human being maintains this concern and how the undergraduate student manages to solve this question and to be comprehensively trained. In this process the questions about what and how to learn? and how to build? will be fundamental.